Nomogram for predicting disease-free survival among a multicenter cohort of Chinese patients with locally advanced rectal cancer - Li ZH (Cancer Management and Research, 2019)
Zhen-Hui Li,1 Pei-Yi Xie,2 Da-Fu Zhang,1 Ya-Jun Li,3,4 Lin Wu,5 Jian Dong,6 Jian Xiao,7 Zai-Yi Liu31Department of Radiology, The Third Affiliated Hospital of Kunming Medical University, Yunnan Cancer Hospital, Kunming 650118, People’s Republic of China; 2Department of Radiology, The Sixth Affiliated Hospital of Sun Yat-sen University, Guangzhou 510655, People’s Republic of China; 3Department of Radiology, Guangdong General Hospital, Guangdong Academy of Medical Sciences, Guangzhou 510080, People’s Republic of China; 4School of Medicine, South China University of Technology, Guangzhou 510641, People’s Republic of China; 5Department of Pathology, The Third Affiliated Hospital of Kunming Medical University, Yunnan Cancer Hospital, Kunming 650118, People’s Republic of China; 6Department of Colorectal Surgery, The Third Affiliated Hospital of Kunming Medical University, Yunnan Cancer Hospital, Kunming 650118, People’s Republic of China; 7Department of Medical Oncology, The Sixth Affiliated Hospital of Sun Yat-sen University, Guangzhou 510655, People’s Republic of ChinaPurpose: This study aimed to develop and validate a nomogram for predicting 3-year disease-free survival (DFS) among a multicenter cohort of Chinese patients with locally advanced rectal cancer (LARC) who underwent preoperative therapy followed by surgery. This nomogram might help identify patients who would benefit from postoperative adjuvant chemotherapy and close follow-up.Materials and methods: All data from 228 patients in two independent Chinese cohorts (118 patients and 110 patients) were pooled and subjected to survival analysis. One cohort’s data were used to develop multivariate nomograms based on Cox regression, and the second cohort was used for external validation. The variables were sex, age, clinical tumor stage, tumor location, preoperative therapy protocol, adjuvant chemotherapy, surgical procedure, surgical approach, pTNM stage, tumor deposit, tumor regression grade, lymphovascular invasion, perineural invasion, pretreatment serum carcinoembryonic antigen (CEA) level, preoperative CEA level, and postoperative CEA level. The model’s performance was evaluated based on its discrimination, calibration, and clinical usefulness.Results: The nomogram was based on ypT stage and ypN stage, and the C-index values for 3-year DFS were 0.70 in the training cohort (95% confidence interval: 0.62–0.78) and 0.78 in the validation cohort (95% confidence interval: 0.68–0.89). The Hosmer-Lemeshow calibration test revealed good calibration for predicting 3-year DFS in the training and validation cohorts, and decision curve analysis demonstrated that the nomogram was clinically useful.Conclusion: This nomogram including the ypT stage and ypN stage could predict DFS at 3 years after surgery, which may help better identify Chinese patients who would benefit from additional postoperative adjuvant systemic treatment.Keywords: rectal cancer, disease-free survival, recurrence, nomogram